Pengaruh Sistem Pengendalian Manajemen, Sistem Informasi Akuntansi dan Gaya Kepemimpinan Terhadap Kinerja Manajerial (Studi Kasus pada Dinas Sosial Kota Jambi) - Yaasmiinah Febriani P. F; Netty Herawaty; Rico Wijaya Z (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of management control systems, accounting information systems, and leadership styles simultaneously and partially on managerial performance at the Social Services Department in Jambi City using a quantitative approach. Data collection techniques were conducted using questionnaires distributed to respondents, and then analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method to test the relationship between variables. The results of the study indicate that simultaneously there is a positive and significant influence between the variables of management control systems, accounting information systems, and leadership styles on managerial performance. However, partially only the accounting information system variable has no significant effect on managerial performance at the Social Services Department in Jambi City.